2016
DOI: 10.1103/physreve.93.062702
|View full text |Cite
|
Sign up to set email alerts
|

Electric field effects on phase transitions in the 8CB liquid crystal doped with ferroelectric nanoparticles

Abstract: The influence of a low ac electric field on phase transitions is discussed in the case of a nematic liquid crystal 4-n-octyl-4^{'}-cyanobiphenyl (8CB) doped with Sn_{2}P_{2}S_{6} ferroelectric nanoparticles. The phase-transition temperatures obtained from temperature-dependent dielectric measurements were higher than those determined by the calorimetric method. This difference is explained by the presence of the measuring electric field which induces two effects. The first one is the amplification of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…This is often achieved by coating the surface with monomolecular organic materials, surfactants (stabiliser), or ligands. For instance, oleic acid, 7,10,17,20,21,[24][25][26][27] selenium docosane 28 and dodecylbenzenesulphonic acid 29,30 have been widely utilized for the coating of NPs.…”
Section: Reznikov Et Al Have Shown That a Low Concentration Of Ferromentioning
confidence: 99%
“…This is often achieved by coating the surface with monomolecular organic materials, surfactants (stabiliser), or ligands. For instance, oleic acid, 7,10,17,20,21,[24][25][26][27] selenium docosane 28 and dodecylbenzenesulphonic acid 29,30 have been widely utilized for the coating of NPs.…”
Section: Reznikov Et Al Have Shown That a Low Concentration Of Ferromentioning
confidence: 99%
“…For f >100 kHz, a dielectric relaxation process begins, thus the phase shift between the field and the polarization occur. Then the dielectric heating causes increase in the temperature of the sample, in turn, decreasing the effective birefringence of the LC medium . The light retardation τ = 2 πd Δ n eff /λ is proportional to the effective birefringence Δ n eff and thickness d at a wavelength (λ).…”
Section: Resultsmentioning
confidence: 99%
“…For the non-harvested nanoparticles dispersed with the 8CB liquid crystal, we previously showed that the volume concentration, f NP ¼ 0.08%, allows optimization of the effects of the nanoparticles. 8,13 Moreover this concentration corresponds to a homogeneous dispersion. For these reasons, this concentration was chosen for nanocolloid #2.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were then introduced in an appropriate heating stage and measurements were made using a Hewlett Packard 4284A Impedance Analyzer covering the frequency range from f ¼ 20 Hz to f ¼ 1 MHz. 13 The amplitude of the measuring sinusoidal electric eld was xed at 0.1 V. For each mixture, a minimum of two samples were measured for each orientation. Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation